Feasibility Study Usaha Gerai Umah Oleh-Oleh Bagansiapiapi Binaan PT PHR dan Polbeng: Peluang, Tantangan, dan Strategi Pengembangan - Arif, Muhammad; Nosa, Muhammad Ridho (Jurnal EMT KITA, 2026)
This study aims to evaluate the feasibility of the Bagansiapiapi Home Souvenir Shop, a business under the auspices of PT Pertamina Hulu Rokan (PHR) and Bengkalis State Polytechnic (POLBENG). Using qualitative and quantitative approaches, the study examined market, technical, managerial, financial, legal, and social aspects. The results indicate that this business is feasible in terms of market opportunities, community support, and financial prospects, despite challenges in digital marketing, product innovation, and managerial capacity. Recommended strategies include strengthening branding, digital promotion, product standardization, and increasing the capacity of MSMEs.